Oil-well lightweight cement slurry for improving compressive strength and hydration rate in low-temperature conditions. (28th November 2022) - Mozaffari, Sajjad; Rahmani, Omeid; Piroozian, Ali; Ziabakhsh-Ganji, Zaman; Mostafavi, Hossein
Graphical abstract: Highlights: LWC presents greater specific surface area, increasing reaction and hydration rate. The shear bonding increased to support the pipe in the wellbore. New RIPI LWC implies that cement columns can be pumped higher in the annulus. Multiple-stage cementing becomes unnecessary without reducing cement integrity. Abstract: Inadequate early compressive strength is a common problem when employing lightweight cement (LWC) slurries during the cementing of oil wells under low-temperature conditions. A new formulation of LWC slurry was investigated by the Research Institute of Petroleum Industry (RIPI) to improve the compressive strength and hydration rate of LWC slurries in low-temperature conditions. In this study, bottom-hole static temperature (BHST) ranges from 21 °C to 82 °C. Halliburton cement friction reducer (CFR-3), Litefil microspheres (D-124), hydroxy ethyl cellulose (D-112), styrene butadiene latex (D-600), and high strength hydrophobic silica (HSL-2) were as lightweight additives to make the RIPI-LWC formulation. The results showed that adding more 5 g of HSL-2 nanoparticles causes in a low-density cement slurry from 1442 kg/m 3 to 1281.5 kg/m 3 . Besides, at the temperature of 21 °C, the strength value (i.e., 3.5 MPa @ 3:56 h)) was developed much faster than the temperature of 82 °C (i.e., 3.5 MPa @ 20:48 h), providing more significant insights into applying the proposed lightweight cement by reducing curing time. Furthermore, the hydraulic bonding of cement slurry was increased by attention to the action of thixotropic additive in preventing the gas migration from the cement slurry. The involvement of the new RIPI-LWC implies that cement columns can be pumped higher in the annulus, multiple-stage cementing becomes unnecessary without reducing cement integrity, and it is more economical and cost-effective than previous RIPI formulations.